Active power losses and energy efficiency analysis of HPS lamps with electromagnetic control gear and electronic ballast under the sinusoidal and nonsinusoidal condition - Roman Sikora; Przemysław Markiewicz; Paweł Rózga (Bulletin of the Polish Academy of Sciences: Technical Sciences, 1921)
Outdoor lighting is an important element in creating an evening and nocturnal image of urban spaces. Properly designed and constructed lighting installations provide residents with comfort and security. One way to improve the energy efficiency of road lighting installation is to replace the electromagnetic control gear (ECG) with electronic ballasts (EB). The main purpose of this article is to provide an in-depth comparative analysis of the energy efficiency and performance of HPS lamps with ECG and EB. It will compare their performance under sinusoidal and nonsinusoidal voltage supply conditions for the four most commonly used HPS lamps of 70 W, 100 W, 150 W, and 250 W. The number of luminaires supplied from one circuit was determined based on the value of permissible active power losses. With the use of the DIALux program, projects of road lighting installation were developed. On this basis, energy performance indicators, electricity consumption, electricity costs, and CO 2 emissions were calculated for one-phase and three-phase installations. The obtained results indicate that an HPS lamp with EB is better than an HPS lamp with ECG in terms of energy quality, energy savings, and environmental impact. The results of this analysis are expected to assist in the choice of HPS lighting technology.